Nivel de conocimientos sobre factores de riesgo del cáncer de cuello uterino y prácticas de prevención, Calemar – Bolívar - Flores Esquivel, María Vanessa (2020)
This research is quantitative, descriptive, correlational, cross-sectional, was carried out during the year 2019 with the purpose of determining the relationship between the level of knowledge about risk factors for cervical cancer and prevention practices in women of the Caserío de Calemar - Bolívar. The sample universe consisted of 70 women to whom two checklist type formats were applied: one to measure the level of knowledge about cervical cancer, and the other to measure prevention practices, obtaining as results that: 81.4% of women have low level of knowledge, 12.9% level of average knowledge and 5.7% level of good knowledge; 87.1% do not carry out prevention practices and 12.9% carry out prevention practices; There is a highly significant relationship X2 = 12.6 p = 0.000 between the level of knowledge and practices of cervical cancer prevention